Peran Orang Tua dalam Meningkatkan Minat Belajar Anak Usia 5-6 Tahun pada Masa Pandemi - Riwayati Zein; Khoirun Nisak; Dini Maielfi (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
Reading comprehension is the ability of process to comprehend the text or massage, its meaning and integrate with the knowledge readers that they have already known. When they read a text, they can obtain much information about knowledge. In fact, the students still not interest in learning reading comprehension, because it’s boring situation and they cannot understand about the text or massage. The interest topic is one of the strategies can be used by the teacher in teaching learning reading subject for students. It increases the students’ motivation and their interest in learning. Students’ interest is come from within students or from their inside. Two types of interest can influence the students’ interest: first, personal interest is the students only focus a specific activity or topic. Second, situational interest is the students’ interest are not permanent depend on the condition stimulate. In learning, the teacher is a control person to manage the students and the teacher should choice the interest topic in teaching reading comprehension.